Can Second-Generation Endogenous Growth Models Explain the Productivity Trends and Knowledge Production in the Asian Miracle Economies? - Ang, James B.; Madsen, Jakob B. (The Review of Economics and Statistics, 2011)
Using data for six Asian miracle economies over the period from 1953 to 2006, this paper examines the extent to which growth has been driven by R&D and tests which second-generation endogenous growth model is most consistent with the data. The results give strong support to Schumpeterian growth theory but only limited support to semi-endogenous growth theory. Furthermore, it is shown that R&D has played a key role for growth in the Asian miracle economies.